Implementasi pewarna alami untuk diversifikasi mie sagu ikan pada pelaku usaha mikro mie sagu di Kabupaten Kepulauan Meranti, Riau - Syahrul Syahrul; Dewita Dewita; Restu Restu (Riau Journal of Empowerment, 2018)
Sago noodles of Selat Panjang have been known by the people of Riau Province and Indonesia, which are produced by microenterprise in the Regency of Kepulauan Meranti. Kepulauan Meranti is one of the largest sago-producing regions in Indonesia and is a marine fish production center. Considering that sago noodle products are rich in carbohydrates but low in protein, it needs innovation to enrich their nutritional value. The purpose of this activity was the application of the microenterprise production of sago noodles with good quality, high nutrition, and to be the superior products. The used method was active participation in learning. The results obtained from this activity that this activity has been carried out well, and the participants had had firsthand experience in processing sago technology enriched with concentrations of fish and natural dyes. This activity has been able to provide insight to partners about products and business development. After the activity, the participants' responses and counseling were very helpful.